(untitled) (ResearchJet Journal of Analysis and Inventions, 2021)
This article analyzes the specifics of the use of information and communication technologies (ICT) in enterprises. During the study, the author suggested ways to effectively use ICT in the structure of the information system and enterprise management, given that the development of information systems in the enterprise, the decision on its structure depends on the diversity and size of information resources of the enterprise.